Corporate democratic nation-building: Reflections on the constructive role of businesses in fostering global democracy. Issue 1 (February 2017) - Anker, Thomas Boysen
Abstract: Europe finds itself in a challenging situation dominated by economic and political uncertainty, which has deep ramifications for businesses and society. The Brexit vote for the UK to leave the EU has caused a political crisis, which raises fundamental questions about the founding mission of the EU as a largescale nation-building experiment aiming at promoting democracy, peace and prosperity across Europe through an "ever closer union among the peoples of Europe". This Reflection on Europe argues that Europe needs to establish a new democratic equilibrium and that businesses can play a fundamental constructive role to achieve this new equilibrium by actively designing core internal and external business activities to be conducive to key enabling conditions of democracy.